薬剤関連顎骨壊死 ポジションペーパー2023 ～改訂のポイント - 森寺, 邦康; 岸本, 裕充 (日本口腔外科学会雑誌, 2024)
Position Paper on Medication-Related Osteonecrosis of the Jaw 2023 has been revised based on the latest findings seven years after the position paper was revised in 2016. The main points of this revision will be focused on seven key points. The first point is that the designation has been changed from ARONJ to MRONJ. The second point is a slight change in diagnostics and staging, with the removal of position 0 from staging. The third point is the incidence of MRONJ at low doses may be higher in Japan than in Europe and the U.S. The fourth point emphasizes odontogenic infection requiring extraction rather than tooth extraction as a risk factor. The fifth point is no evidence for the usefulness of antiresorptive agent (ARA) withdrawal in preventing MRONJ, and it was suggested that, in principle, ARA withdrawal should not be used prior to tooth extraction. The sixth point is that surgical treatment has become a higher priority. The seventh point is importance of medical-dental-pharmaceutical collaboration was emphasized.